2014
DOI: 10.31899/hiv9.1003
|View full text |Cite
|
Sign up to set email alerts
|

Formative research to develop an intervention for addressing mental health/psychosocial issues and HIV vulnerability of marginalized adolescents in Addis Ababa, Ethiopia

Abstract: HIVCore improves the efficiency, effectiveness, scale, and quality of HIV treatment, care, and support, and prevention of mother-to-child transmission (PMTCT) programs. The Task Order is led by the Population Council in partnership with the Futures Group, the Elizabeth Glaser Pediatric AIDS Foundation, and the University of Washington.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 18 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…It was a formative study that included a qualitative needs assessment to determine the type and extent of mental health and psychological needs among adolescent migrants living in Addis Ababa. This study found sexual abuse among migrant adolescents linked to psychological trauma (Jani and Schenk 2014). In addition, the majority of young migrants experienced social isolation and unstable living situations and engaged in high risk sexual behavior.…”
Section: Development Of Mental Health Screening Tool and Targeted Intmentioning
confidence: 70%
See 3 more Smart Citations
“…It was a formative study that included a qualitative needs assessment to determine the type and extent of mental health and psychological needs among adolescent migrants living in Addis Ababa. This study found sexual abuse among migrant adolescents linked to psychological trauma (Jani and Schenk 2014). In addition, the majority of young migrants experienced social isolation and unstable living situations and engaged in high risk sexual behavior.…”
Section: Development Of Mental Health Screening Tool and Targeted Intmentioning
confidence: 70%
“…In addition, the majority of young migrants experienced social isolation and unstable living situations and engaged in high risk sexual behavior. Additionally, few migrant adolescents displayed comprehensive HIV prevention knowledge (Jani and Schenk 2014). Based on these findings the study expert committee developed a targeted counseling intervention consisting of individual and group counseling sessions, art and creative therapy, and community engagement events.…”
Section: Development Of Mental Health Screening Tool and Targeted Intmentioning
confidence: 99%
See 2 more Smart Citations
“…Formative research enables understanding of the nature of the problem and the programme responses to address it [1,13,14] and determination of the priority target population [15,16], as well as assessing their needs and perceptions regarding the problem and the proposed intervention. Formative research also fosters an understanding of how the new intervention will be introduced into existing services [6,17,18], the potential role of various actors in delivering the intervention and additional elements required for the intervention [19].…”
Section: Formative Researchmentioning
confidence: 99%